Adsorption Thermodynamics of Methyl Orange from Aqueous Solution onto a Hyper-Cross-Linked Polystyrene Resin Modified with Phenolic Hydroxy Groups - Jianhan Huang (Adsorption Science & Technology)
A novel hyper-cross-linked polystyrene resin, HJ-P01, was prepared and its structure characterized via nitrogen adsorption/desorption isotherms, its residual chlorine content and its Fourier-transform infrared (FT-IR) spectrum. The adsorption isotherms of Methyl Orange from aqueous solution onto HJ-P01 resin were subsequently measured and the corresponding thermodynamic parameters calculated. The results indicated that HJ-P01 resin possessed a micro-/meso-porous structure, with its surface being chemically modified by phenolic hydroxy groups. The resin was capable of the effective adsorption of Methyl Orange from aqueous solution, although its adsorption capacity decreased with increasing temperature. The adsorption isotherms could be fitted by the Freundlich isotherm model and the adsorption was shown to be a spontaneous, exothermic process leading to a more ordered system.